Prophylactic antigen‐specific T‐cells targeting seven viral and fungal pathogens after allogeneic haemopoietic stem cell transplant. Issue 3 (15th March 2021) - Gottlieb, David Jonathan; Clancy, Leighton Edward; Withers, Barbara; McGuire, Helen Marie; Luciani, Fabio; Singh, Mandeep; Hughes, Brendan; Gloss, Brian; Kliman, David; Ma, Chun Kei Kris; Panicker, Shyam; Bishop, David; et al.
Abstract: Objectives: Adoptive immunotherapy using donor‐derived antigen‐specific T‐cells can prevent and treat infection after allogeneic haemopoietic stem cell transplant (HSCT). Methods: We treated 11 patients with a prophylactic infusion of 2 × 10 7 cells per square metre donor‐derived T‐cells targeting seven infections (six viral and one fungal) following HSCT. Targeted pathogens were cytomegalovirus (CMV), Epstein–Barr virus (EBV), adenovirus, varicella zoster virus, influenza, BK virus (BKV) and Aspergillus fumigatus . Results: T‐cell products were successfully generated in all patients with 10 products responsive to 6 or 7 infections. T‐cell infusions were associated with increases in antigen‐experienced activated CD8 + T‐cells by day 30. CMV, EBV and BKV reactivation occurred in the majority of patients and was well controlled except where glucocorticoids were administered soon after T‐cell infusion. Three patients in that circumstance developed CMV tissue infection. No patient required treatment for invasive fungal infection. The most common CMV and EBV TCR clonotypes in the infusion product became the most common clonotypes seen at day 30 post‐T‐cell infusion. Donors and their recipients were recruited to the study prior to transplant. Grade III/IV graft‐versus‐host disease developed in four patients. At a median follow‐up of 390 days post‐transplant, six patients had died, 5 of relapse, and 1 of multi‐organ failure. Infection did not contribute to death in any patient. Conclusion: Rapid reconstitution of immunity to a broad range of viral and fungal infections can be achieved using a multi‐pathogen‐specific T‐cell product. The development of GVHD after T‐cell infusion suggests that infection‐specific T‐cell therapy after allogeneic stem cell transplant should be combined with other strategies to reduce graft‐versus‐host disease. Abstract : In this study, 12 patients were treated with ex vivo expanded donor‐derived T‐cells specific for seven virus and fungal pathogens. There was no acute infusion‐related toxicity. CD8 T‐cell numbers in the peripheral blood rose within 30 days of infusion. Graft‐versus‐host disease and corticosteroid use were associated with viral reactivation; no patient developed fungal disease. Relapse ( n  = 5) and multi‐organ failure ( n  = 1) were the causes of death. Infection did not contribute to death in any patient.